Kevin Lygo, The Emperors of Byzantium, with introduction by Bettany Hughes and foreword by Robert Peston. - Westbrook , Nigel (Journal of Greek Archaeology, 2024)
In the popularization of archaeology and ancient history through various media, we are familiar with many accounts of the Greek achievements, of the Roman Empire, and intertwined with it, of ancient Egypt. The strange world of Byzantium, by contrast, lacks either a sustained interest in its archaeology by the public, or the adoption of its history in popular culture. Coinciding with the West’s dark ages, Byzantium is by contrast too ‘Eastern’. Even within academia, Byzantium is often subsumed by ‘Christian history’. While it is known to specialists, the fact that Byzantines saw themselves as Romaoi, Romans, generally escapes popular consciousness. There have been attempts to remedy this aporia.